2021
DOI: 10.1152/ajpendo.00655.2020
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of bone fragility by pulsed electromagnetic fields in type 2 diabetic KK-Ay mice involving Wnt/β-catenin signaling

Abstract: Type 2 diabetes mellitus (T2DM) results in compromised bone microstructure and quality, and subsequently increased risks of fractures. However, it still lacks safe and effective approaches resisting T2DM bone fragility. Pulsed electromagnetic fields (PEMF) exposure has proven to be effective in accelerating fracture healing and attenuating osteopenia/osteoporosis induced by estrogen deficiency. Nevertheless, whether and how PEMF resist T2DM-associated bone deterioration remain not fully identified. The KK-Ay m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…Several studies in rodent models of T2D, with compromised bone quality and strength, have reported effects of diabetes on osteocytes. For example, various types of physical activity (e.g., wheel running, swimming, pulsed electromagnetic field stimulation) represent stimuli that, as noted earlier, produce biomechanical loads and forces sensed by osteocytes; thus, exercise has been shown to act as an effective countermeasure to prevent or reverse T2D-related skeletal fragility [41,42,43 ▪ ]. Interestingly, in the study that used pulsed electromagnetic field stimulation, T2D-induced osteocyte apoptosis was alleviated and sclerostin levels were reduced suggesting that exercise maintains a healthy osteocyte lacuno-canalicular network in the context of T2D [43 ▪ ].…”
Section: Effects Of Type 2 Diabetes On Osteocytesmentioning
confidence: 82%
See 1 more Smart Citation
“…Several studies in rodent models of T2D, with compromised bone quality and strength, have reported effects of diabetes on osteocytes. For example, various types of physical activity (e.g., wheel running, swimming, pulsed electromagnetic field stimulation) represent stimuli that, as noted earlier, produce biomechanical loads and forces sensed by osteocytes; thus, exercise has been shown to act as an effective countermeasure to prevent or reverse T2D-related skeletal fragility [41,42,43 ▪ ]. Interestingly, in the study that used pulsed electromagnetic field stimulation, T2D-induced osteocyte apoptosis was alleviated and sclerostin levels were reduced suggesting that exercise maintains a healthy osteocyte lacuno-canalicular network in the context of T2D [43 ▪ ].…”
Section: Effects Of Type 2 Diabetes On Osteocytesmentioning
confidence: 82%
“…For example, various types of physical activity (e.g., wheel running, swimming, pulsed electromagnetic field stimulation) represent stimuli that, as noted earlier, produce biomechanical loads and forces sensed by osteocytes; thus, exercise has been shown to act as an effective countermeasure to prevent or reverse T2D-related skeletal fragility [41,42,43 ▪ ]. Interestingly, in the study that used pulsed electromagnetic field stimulation, T2D-induced osteocyte apoptosis was alleviated and sclerostin levels were reduced suggesting that exercise maintains a healthy osteocyte lacuno-canalicular network in the context of T2D [43 ▪ ]. Furthermore, given that increased circulating sclerostin levels have been consistently reported in human T2D patients [44–46], antisclerostin antibodies may mimic the effects of exercise by reversing T2D-related skeletal fragility as shown by a preclinical study in rats with T2D [47].…”
Section: Effects Of Type 2 Diabetes On Osteocytesmentioning
confidence: 82%
“…The application of PEMF treatment for patients with osteoporosis can significantly increase bone density and prevent bone loss ( 141 , 142 ). Studies on animal models of diabetes found that LIPEMF can restore the expression of Runx2 through the Wnt/β-catenin signaling pathway and reverse the deterioration of bone microstructure and strength, thereby preventing bone loss caused by diabetes, but has no effect on osteoclasts ( 143 145 ). The positive effect of LIPEMF in promoting bone healing has been confirmed in a large number of experiments.…”
Section: Physical Therapiesmentioning
confidence: 99%
“…1 The US Food and Drug Administration approved PEMFs as a safe and effective means for treating non-unions and osteoporosis based upon multicenter, randomized and prospective clinical studies in 1970s. [2][3][4] Additionally, results from experimental work have shown that in addition to improving bone quality and strength and promoting osteogenesis, [5][6][7][8] PEMFs also inhibit osteoclastic resorption with no stated side effects. 9 However, despite all these, the clinical promotion and application of PEMFs has not been as ideal as people had originally expected so far.…”
Section: Introductionmentioning
confidence: 99%